Establishment of Anopheles stephensi in a former Anopheles arabiensis Sterile Insect Technique project area in northern Sudan - Amgad Ali Mairgani; Obidallah Mohamed Obidallah; Abdelrahman Abdelal Mohamed Abadi; Salma Ahmed Ramadan; Marc S Halfon; Rasha Siddig Azrag (Transactions of The Royal Society of Tropical Medicine and Hygiene, 2026)
Abstract Background Northern Sudan has historically maintained low seasonal malaria transmission due to the arid environment and river-regulated vector population. The present study documents the establishment of the invasive Anopheles stephensi in a former Sterile Insect Technique (SIT) project area in northern Sudan. Methods Longitudinal entomological surveys of Anopheles larvae and indoor resting adults were conducted in Merowe, Dongola and Halfa localities in northern Sudan during the 2022 flooding phase of the Nile, with systematic sampling of both adults and larval stages. Results Of the 1251 Anopheles mosquitoes identified, A. stephensi comprised 28.6% of specimens, indicating an established population across Merowe and Dongola, with the highest estimated density at Merowe (36.4%). A. stephensi demonstrated significant co-occurrence with Anopheles arabiensis across all positive larval habitats (p<0.001) and was found primarily in artificial, vegetation-free water bodies. This study represents the first documentation of ground seepage as a major Anopheles larval habitat in northern Sudan. Conclusions The study documents an epidemiological transition from historically river-regulated malaria transmission to a transmission system increasingly dominated by anthropogenic water sources associated with infrastructure development. The establishment of A. stephensi indicates a potential compromise of natural isolation barriers that underpinned the former SIT project and suggests that passive transportation may facilitate dispersal across geographic barriers, while climate change and expanded agricultural irrigation projects further compound transmission risk.